Revitalisasi Kompetensi Pelatih Olahraga Melalui Pelatihan Dasar Berbasis Kompetensi di Muaro Jambi - Yuliawan, Ely; Sukendro, Sukendro; Khairunnisa, Fitri; Yusradinafi, Yusradinafi; Munar, Hendrika; Aslina, Cut Vidya (Jurnal Pengembangan dan Pengabdian Masyarakat, 2026)
This community service activity aims to revitalize the competencies of sports coaches in Muaro Jambi Regency through competency-based basic training tailored to the needs of each sport branch. The activity is carried out in the BKD Hall of Muaro Jambi Regency involving 56 participants consisting of coaches from various sports branches, in collaboration with KONI Muaro Jambi Regency as the implementing partner. The background of this activity is the continued presence of coaches with limited knowledge of coaching methodology, a lack of understanding of modern training principles, and low adaptability to the specific needs of sports branches. The activity methods include coach needs analysis, development of competency-based training modules, delivery of material by expert speakers, as well as hands-on practice and reflective discussion. The results of the activities indicate a significant improvement in participants' understanding of the basic principles of coaching, training programme planning, and the ability to apply approaches appropriate to the characteristics of the sports being coached. In addition, coaches also gained new skills in training management, athlete performance evaluation, and the development of performance-oriented coaching strategies. Thus, these activities have successfully had a positive impact on enhancing the quality of human resources in sports in Muaro Jambi Regency, while also serving as a model for developing coaches who are adaptive to the needs and dynamics of regional sports coaching.